The Effect of Phyto-Lecithin on Preservation and Cryopreservation of Semen: A Review - Aku, AS; Sandiah, N; Sadsoeitoeboen, PD; Amin, R; Herdis, Herdis (ANIMAL PRODUCTION, 2007)
Artificial insemination represents one of technologies in livestock reproduction that can be applied to cattle, sheep, goats and other livestock. Application of livestock reproduction technology includes artificial insemination to increase reproductive efficiency. Semen processing is one critical phase in an artificial insemination program. The use of animal origin ingredient for semen extenders, such as egg yolk and milk, presents a risk of microbial contamination, which lead to the search for alternatives. To increase standard of quality, researchers exploits phyto-lesitin for semen extender and the results showed no significant differences in motility, viability, and acrosomal status of spermatozoa with phyto-lesitin extender when compared to tris-egg yolk-containing extenders. (Animal Production 9(1): 49-52 (2007)Â Key Words : Phyto-Lechitin, preservation, cryopreservation, semen